Biomarkers related to respiratory symptoms and lung function in adults with asthma. (20th February 2018) - Calciano, Lucia; Portas, Laura; Corsico, Angelo Guido; Olivieri, Mario; Degan, Paolo; Ferrari, Marcello; Fois, Alessandro; Pasini, Anna Maria Fratta; Pasini, Andrea; Zanolin, Maria Elisabetta; de Marco, Roberto; Accordini, Simone
Abstract: Background : There is a need for easily measurable biomarkers that are able to identify different levels of asthma severity. Aim : To assess the association between peripheral blood cell counts, fractional nitric oxide in exhaled air (FeNO), urinary biomarkers of oxidative stress (8-hydroxy-2′-deoxyguanosine and 8-isoprostane), and asthma severity in adult patients from the general population. Methods : In the Gene Environment Interactions in Respiratory Diseases study, 287 subjects with asthma (aged 20–64) were identified from the general population in Verona (Italy) (2008–2010). Self-reported asthma attacks, asthma-like symptoms and the use of hospital services in the past year were synthesized in a score of respiratory symptoms (SRS). The association of biomarkers with SRS and lung function measures (pre-bronchodilator FEV1 % predicted and FEV1 /FVC) was assessed using quasi-Poisson and Gaussian regression models, respectively. Results : Eosinophils (ratio of expected scores: RES[95%CI] = 1.19[1.09, 1.30]), basophils (RES[95%CI] = 1.24[1.10, 1.40]), lymphocytes (RES[95%CI] = 1.27[1.12, 1.45]) and FeNO (RES[95%CI] = 1.18[1.02, 1.37]) were positively associated with SRS. However, only eosinophils (RES[95%CI] = 1.15[1.02, 1.30]) and lymphocytes (RES[95%CI] = 1.25[1.06, 1.47]) showed an independent association. Furthermore, eosinophils (change in the expected outcome for 1-SD increase: CEO[95%CI] = −1.18[−2.09, −0.27]%), basophils (CEO[95%CI] = −1.24[−2.16, −0.33]%) and lymphocytes (CEO[95%CI] = −1.07[−1.99, −0.14]%) were individually, but not independently, associated with FEV1 /FVC. Finally, neutrophils were negatively associated with FEV1 % predicted (CEO[95%CI] = −2.22[−4.00, −0.44]%). Conclusions : We identified a pattern of association between a set of biomarkers and asthma endotypes in adult patients from the general population, which could improve understanding of the heterogeneity and severity of the disease and could be useful in defining targeted therapeutic approaches.